2022
DOI: 10.48550/arxiv.2208.02782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Panchromatic evolution of three luminous red novae: Forbidden hugs in pandemic times -- IV

Abstract: We present photometric and spectroscopic data on three extragalactic luminous red novae (LRNe): AT 2018bwo, AT 2021afy, and AT 2021blu. AT 2018bwo was discovered in NGC 45 (at about 6.8 Mpc) a few weeks after the outburst onset. During the monitoring period, the transient reached a peak luminosity of 10 40 erg s −1 . AT 2021afy, hosted by UGC 10043 (∼ 49.2 Mpc), showed a double-peaked light curve, with an early maximum reaching a luminosity of 2.1 × 10 41 erg s −1 . Finally, for AT 2021blu in UGC 5829 (∼ 8.6 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Using v E ≈ 500 km s −1 and Equation (2) gives the recombining ejecta mass M ej ≈ 10 M e , although the estimate is very sensitive to the assumed ejecta velocity. Again similarly to ZTF 21aancgbm, here recombination alone is not sufficient to explain the luminosity of the plateau, and Equation (3) implies interaction with pre-existing mass Pastorello et al (2022) discuss archival HST and ground-based imaging of this transient, and the properties of the putative progenitor. We note that, in addition to the data presented in their paper, this transient has archival Spitzer Space Telescope/IRAC imaging from 2007 December 27.…”
Section: Lrn-goldmentioning
confidence: 83%
See 1 more Smart Citation
“…Using v E ≈ 500 km s −1 and Equation (2) gives the recombining ejecta mass M ej ≈ 10 M e , although the estimate is very sensitive to the assumed ejecta velocity. Again similarly to ZTF 21aancgbm, here recombination alone is not sufficient to explain the luminosity of the plateau, and Equation (3) implies interaction with pre-existing mass Pastorello et al (2022) discuss archival HST and ground-based imaging of this transient, and the properties of the putative progenitor. We note that, in addition to the data presented in their paper, this transient has archival Spitzer Space Telescope/IRAC imaging from 2007 December 27.…”
Section: Lrn-goldmentioning
confidence: 83%
“…Three of these have been studied in detail previously: ZTF 18acbwfza (AT 2018hso; Cai et al 2019Pastorello et al 2021a), andZTF 20aawdwch (AT 2020hat;Pastorello et al 2021b). Three other transients-ZTF 21aancgbm (AT 2021biy; Cai et al 2022), ZTF 21aagppzg (AT 2021blu; Pastorello et al 2022), and ZTF 21acpkzcc (AT 2021aess; Davis et al 2021)-were identified as possible LRNe in 2021. We initiated optical and NIR photometric and spectroscopic follow-up campaigns for these objects, which confirmed their nature as LRNe.…”
Section: Lrn-goldmentioning
confidence: 99%
“…We searched the literature for the masses of the quiescent progenitors of all LRNe for which that parameter was estimated, while for consistency we measured the V-band absolute magnitude (M V ) at the red peak (or in the plateau for those objects that do not show a second peak) for all objects 14 . The absolute magnitude and progenitor mass values we used are reported in Table A.4 (see Pastorello et al 2022, for the relative references). Even though for only 9 objects 15 the progenitor mass was well estimated from pre-explosion images or modeling of the light curves, we see a clear linear correlation between these two parameters.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The remarkable cases of this class are as follows: M31-RV, NGC4490-2011OT1, NGC3437-2011OT1, UGC12307-2013OT1, AT 2014ej, SNhunt248 2 , M31-LRN2015, AT 2015dl/M101-2015OT1, AT 2017jfs, AT 2018bwo, AT 2018hso, AT 2019zhd, AT 2020hat, AT 2020kog, AT 2020hat, AT 2021biy, AT 2021afy and AT 2021blu. [14,15,116,[124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142]. Most LRNe are located in spiral to irregular galaxies.…”
Section: Luminous Red Novaementioning
confidence: 99%
“…This dramatic spectral evolution behaviour (see the right panel of Figure 6) can be a diagnostic tool to discriminate LRNe from other gap transients, such as LBV outbursts and ILRTs. Several authors (e.g., [136,139,140,142,144,154,155]) looked for the possible correlations among the photometric and spectroscopic observables for LRNe. They obtained similar results: higher-luminosity events have longer evolution; hotter, larger, and higher-velocity photospheres; along with luminous Hα lines.…”
Section: Luminous Red Novaementioning
confidence: 99%